Contamination of firefighter personal protective equipment and skin and the effectiveness of decontamination procedures. Issue 10 (3rd October 2017) - Fent, Kenneth W.; Alexander, Barbara; Roberts, Jennifer; Robertson, Shirley; Toennis, Christine; Sammons, Deborah; Bertke, Stephen; Kerber, Steve; Smith, Denise; Horn, Gavin
ABSTRACT: Firefighters' skin may be exposed to chemicals via permeation/penetration of combustion byproducts through or around personal protective equipment (PPE) or from the cross-transfer of contaminants on PPE to the skin. Additionally, volatile contaminants can evaporate from PPE following a response and be inhaled by firefighters. Using polycyclic aromatic hydrocarbons (PAHs) and volatile organic compounds (VOCs) as respective markers for non-volatile and volatile substances, we investigated the contamination of firefighters' turnout gear and skin following controlled residential fire responses. Participants were grouped into three crews of twelve firefighters. Each crew was deployed to a fire scenario (one per day, four total) and then paired up to complete six fireground job assignments. Wipe sampling of the exterior of the turnout gear was conducted pre- and post-fire. Wipe samples were also collected from a subset of the gear after field decontamination. VOCs off-gassing from gear were also measured pre-fire, post-fire, and post-decon. Wipe sampling of the firefighters' hands and neck was conducted pre- and post-fire. Additional wipes were collected after cleaning neck skin. PAH levels on turnout gear increased after each response and were greatest for gear worn by firefighters assigned to fire attack and to search and rescue activities. Field decontamination using dish soap, water, and scrubbing was able to reduce PAH contamination on turnout jackets by a median of 85%. Off-gassing VOC levels increased post-fire and then decreased 17–36 min later regardless of whether field decontamination was performed. Median post-fire PAH levels on the neck were near or below the limit of detection (< 24 micrograms per square meter [µg/m 2 ]) for all positions. For firefighters assigned to attack, search, and outside ventilation, the 75 th percentile values on the neck were 152, 71.7, and 39.3 µg/m 2, respectively. Firefighters assigned to attack and search had higher post-fire median hand contamination (135 and 226 µg/m 2, respectively) than other positions (< 10.5 µg/m 2 ). Cleansing wipes were able to reduce PAH contamination on neck skin by a median of 54%.